Development of biodegradation process for Poly(DL-lactic acid)degradation by crude enzyme produced by Actinomadura keratinilytica strain T16-1 - Titiporn Panyachanakul (2019)
© 2019 Background: Plastic waste is a serious problem because it is difficult to degrade, thereby leading to global environment problems. Poly(lactic acid)(PLA)is a biodegradable aliphatic polyester derived from renewable resources, and it can be degraded by various enzymes produced by microorganisms. This study focused on the scale-up and evaluated the bioprocess of PLA degradation by a crude microbial enzyme produced by Actinomadura keratinilytica strain T16-1 in a 5 L stirred tank bioreactor. Results: PLA degradation after 72 h in a 5 L bioreactor by using the enzyme of the strain T16-1 under controlled pH conditions resulted in lactic acid titers (mg/L)of 16,651 mg/L and a conversion efficiency of 89% at a controlled pH of 8.0. However, the PLA degradation process inadvertently produced lactic acid as a potential inhibitor, as shown in our experiments at various concentrations of lactic acid. Therefore, the dialysis method was performed to reduce the concentration of lactic acid. The experiment with a dialysis bag achieved PLA degradation by weight loss of 99.93%, whereas the one without dialysis achieved a degradation of less than approximately 14.75%. Therefore, the dialysis method was applied to degrade a commercial PLA material (tray)with a conversion efficiency of 32%, which was 6-fold more than that without dialysis. Conclusions: This is the first report demonstrating the scale-up of PLA degradation in a 5 L bioreactor and evaluating a potential method for enhancing PLA degradation efficiency. How to cite: Panyachanakul T, Sorachart B, Lumyong S, et al. Development of biodegradation process for Poly(DL-lactic acid)degradation by crude enzyme produced by Actinomadura keratinilytica strain T16-1. Electron J Biotechnol 2019;40. https://doi.org/10.1016/j.ejbt.2019.04.005